Nanotechnology in aerospace and structural mechanics - Ramdani, Noureddine, 1986- (Advances in chemical and materials engineering (ACME) book series., 2019)
"This book provides the latest developments in the field of space research and structural mechanics. It also explores the mechanics of nanomaterials, the advancement of their electronic properties, the development of the methods of synthesis of the nanomaterials for fabricating nanodevices, and related technological expertise to assemble the nano components for fabricating the devices"--